2013
DOI: 10.1097/scs.0b013e31828b743b
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life in Children With Cleft Lip and Palate

Abstract: Considering the essential need for oral health-related quality-of-life measures for patients with craniofacial malformations, the current study aimed to investigate the oral health-related quality of life of Iranian patients with cleft lip and palate. Fifty children referred to Cleft lip/Palate Research Center of Mashhad Dental School (Iran) were recruited. Participants were asked to complete the Child Oral Health Impact Profile questionnaire. The questionnaire comprised 38 items and was divided over 5 subscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 16 publications
4
20
0
3
Order By: Relevance
“…In contrast, a study by Broder and colleagues established that with increasing age, females had poorer socio‐emotional well‐being compared to males . Similar findings were reported in an Iranian study, where females had lower emotional well‐being compared to males …”
Section: Discussionsupporting
confidence: 61%
“…In contrast, a study by Broder and colleagues established that with increasing age, females had poorer socio‐emotional well‐being compared to males . Similar findings were reported in an Iranian study, where females had lower emotional well‐being compared to males …”
Section: Discussionsupporting
confidence: 61%
“…Overall, females appear to be more sensitive to perception of different levels of overall and oral health than males [17][18][19].This finding is consistent with the literature, as women tend to be more dissatisfied with their facial appearance; furthermore, females with CLP tend to experience worse quality of life than males with the same condition [20]. Women are also more concerned with health overall, tend to ascribe greater value to medical attention, and better understand the concept that quality of life is associated with health and diseas [18].…”
Section: Discussionmentioning
confidence: 99%
“…Grollemund et al [9] and François-Fiquet et al [4] confirmed that although patients with bilateral FLP are functionally satisfied with their speech, swallowing, and hearing, they are significantly dissatisfied with their appearance, particularly Quality of Life in Adolescents with Cleft Lip and Palate DOI: http://dx.doi.org /10.5772/intechopen.91348 in the upper lip and nose. This dissatisfaction with the esthetic result may even be an early sign of depression [37].…”
Section: Orofacial Functions and Quality Of Lifementioning
confidence: 99%
“…This otherness and especially the differences in appearance often involve varying degrees of facial scars, and dentition variations, such as missing teeth, limitation of speech, and language [7][8][9].…”
Section: Introductionmentioning
confidence: 99%